2023
DOI: 10.1021/acs.macromol.3c00033
|View full text |Cite
|
Sign up to set email alerts
|

ToF-SIMS Depth Profiling to Measure Nanoparticle and Polymer Diffusion in Polymer Melts

Abstract: We apply time-of-flight secondary ion mass spectroscopy (ToF-SIMS) and cross-sectioned trilayer samples to separately measure nanoparticle (NP) and polymer diffusion on micrometer length scales in polymer melts. We fabricate polymer/ diffusing medium/polymer trilayer samples and measure the cross section to extract the NP or deuterated polymer distribution in 3D using ToF-SIMS. After correcting the data for sample tilt, deconvoluting the beam resolution, and integrating the data to extract 1D concentration pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…If an adsorbed polymer layer of the order of R g was added to the NP radius, then the derived diffusion coefficient agreed with SE predictions . These results were recently reproduced using time-of-flight secondary ion mass spectroscopy . Another recent study on attractive PNC systems has shown a similar suppression in diffusion (relative to SE predictions), in unentangled polymers, through dynamic light scattering measurements.…”
Section: Introductionsupporting
confidence: 58%
“…If an adsorbed polymer layer of the order of R g was added to the NP radius, then the derived diffusion coefficient agreed with SE predictions . These results were recently reproduced using time-of-flight secondary ion mass spectroscopy . Another recent study on attractive PNC systems has shown a similar suppression in diffusion (relative to SE predictions), in unentangled polymers, through dynamic light scattering measurements.…”
Section: Introductionsupporting
confidence: 58%
“…Dynamic SIMS is a well-established technique for measuring polymer interfaces and more recently applied to particle diffusion. , …”
Section: Methodsmentioning
confidence: 99%
“…Specific solution concentrations and spin-coating conditions for each layer are listed in Tables S2 and S3. Similar to our previous report, each PNC layer was transferred to a P2VP base layer by etching the spun coat PNC layer off the SiO 2 wafer using a 20 wt % NaOH solution, resulting in a floating PNC film that can be rinsed with DI water and stacked on top of the P2VP base layer. The top P2VP layer was transferred to the bilayer similarly.…”
Section: Introductionmentioning
confidence: 94%
“…Building upon our earlier study, we crafted trilayer samples composed of a thin PNC layer placed between two thick P2VP matrix layers. Upon annealing, NPs diffuse into the homopolymer layers and we measure the NP tracer diffusion coefficient, D NP .…”
Section: Introductionmentioning
confidence: 99%